Effect of substrate composition and drying process on Metarhizium rileyi Nm017’s conidia quality for control of Helicoverpa zea (2019)
The drying process is an important step during the production process of biopesticides. Nonetheless, this process causes a stress condition associated to loss of water; resulting a decrease of enzymatic activity, viability, and virulence in case of entomopathogenic fungi. Thus, suitable conditions must be implemented through the entire process to improve desiccation tolerance and keep stable cells. Therefore, the aim of this work was to evaluate several medium compositions in solid-state fermentation (T1, T2, T3, T4, and T5), and determine the e ect on viability, induction of enzymatic activity, and virulence of dried conidia.